Feuds and State Formation, 1550-1700 The Backcountry of the Republic of Genoa - Raggio, Osvaldo (Early Modern History: Society and Culture, 2018)
This book re-evaluates the role of local agency and provides a new perspective to the political, social and cultural history of state formation, taking a microhistorical approach and through close analysis of archival sources between 1550 to 1700. The backcountry of the Republic of Genoa is a laboratory for gauging the weight and significance of two elements which, according to Charles Tilly and other scholars, have characterized the construction of the modern state: judicial administration and fiscal extraction. The instruments employed in this respect were arbitration and compensation. Interactions between center and periphery occurred within a stratified and discontinuous fabric of fluid jurisdictions and segmented residential topographies, which constituted spaces of mediation. Such spaces were generated by conflicts between kin groups (feuds and factional alignments) and managed both by Genoese officials and by local notables and notaries, who translated a whole set of local practices into judicial procedures. This book offers a rich contextualization of material life, family relationships, economic activities, and power struggles in a corner of the Mediterranean world that was extremely important, but about which very little has been published in English. .